Adaptations and mechanisms underlying plant resilience to drought: Opportunities, challenges, and prospects for water-saving agriculture - Batool, Asifa; Li, Shi-Sheng; Li, Meng-Yao; Tu, Wei; Dong, Hong-Jin; Chu, Xiang- Yuan; He, Sen; Zhang, Jian; Sheng, Hong-Bin; He, Xin-Yi; Lan, Deng-Yao; Xiao, Yun-Li; et al. (International Journal of Applied and Experimental Biology, 2026)
One of the major obstacles to plant growth and productivity, outside of today's crop-growing zones, is drought. Due to acknowledged changes in the global climate, it will become more significant in areas of the world where the issue was previously insignificant. Considering the mechanisms underlying resistance to water deficit and the plants' effective water use is essential to addressing current concerns about enhancing plant genotypes and cultural practices for drought-affected locations. Main barriers to carbon uptake and the metabolic processes that influence how plants react to water scarcity, either alone or in combination with other stressors, are covered in this work. For crops that suffer from drought, oxidative stress is essential. Detoxifying mechanisms play a key role in preventing irreparable damage to redox molecules and photosynthetic machinery as a result of local or systemic signals. The ability of plants, particularly those that embed functional proteins, to prevent or fix membrane damage that occurs throughout the processes of dehydration and rehydration is essential to maintain the integrity of the membranes. These proteins include water transporters, whose function in controlling the water status of plants and moving other metabolites is being thoroughly studied. Over ten years ago, long-distance chemical signaling began to unravel as a primary response to water deficit. In light of new management strategies, the distribution and absorption of carbon and its assimilates among non-reproductive and reproductive parts are reviewed and examined. Enhancement of water-use efficiency in plants, consistent production, and better quality in products are all intended outcomes of these applications. It has already been feasible to discover important genes that can change metabolic processes, and boost the tolerance of plants to drying conditions by studying mechanisms underlying successful response to dehydration and rehydration. This study provides a summary of the most significant information on this subject, including water transporters and engineering for C4 characteristics. Promising technologies, including the modification of crops by genetic engineering via the transfer of regulatory and functional genes, are highlighted.